Angular momentum compensation manipulation to room temperature of the ferrimagnet Ho3−xDyxFe5O12 detected by the Barnett effect - Imai, Masaki; Chudo, Hiroyuki; Ono, Masao; Harii, Kazuya; Matsuo, Mamoru; Ohnuma, Yuichi; Maekawa, Sadamichi; Saitoh, Eiji (Applied physics letters, 2019)
We demonstrate that the angular momentum compensation temperature TA, at which the net angular momentum in the sample disappears, can be controlled in Ho3Fe5O12 by partially substituting Dy for Ho. TA can be detected using the Barnett effect, by which mechanical rotation magnetizes an object due to spin-rotation coupling. We found that TA increases with the Dy content and clarified that TA of Ho1.5Dy1.5Fe5O12 coincides with room temperature. The Barnett effect enables us to explore materials applicable to magnetic devices utilizing the angular momentum compensation only by rotating the powder sample at room temperature.